2012
DOI: 10.1007/s13205-012-0088-y
|View full text |Cite
|
Sign up to set email alerts
|

Leucine to proline substitution by SNP at position 197 in Caspase-9 gene expression leads to neuroblastoma: a bioinformatics analysis

Abstract: To understand the role of CASP9 (Caspase-9) gene products in relation to neuroblastoma disease, we have analyzed the single nucleotide polymorphisms (SNPs) associated with this gene. This can help us understand the genetic variations that can alter the function of the gene products. A total of 941 SNPs are investigated for CASP9 gene. To determine whether a non-synonymous SNP (nsSNP) in this gene affects its protein product, we used certain computational tools which predicted one nsSNP, rs1052574, to have dele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 63 publications
(102 reference statements)
0
4
0
Order By: Relevance
“…Replacement of P199 with L can turn Key-coil into a random coil (Krieger et al, 2005). Similar L to P substitutions with subsequent structural alterations are recognized human cancer markers (Kundu et al, 2013). We also found that 5 of the 30 SO-2 isolates were “Exceptional” in having an antrum-like median pH 50 of 4.4 (Figures 3A and 3B) but corpus-like affinities 20-fold and 50-fold higher than other antrum isolates at pH 6 and pH 4, respectively (Figure S3E).…”
Section: Resultsmentioning
confidence: 88%
“…Replacement of P199 with L can turn Key-coil into a random coil (Krieger et al, 2005). Similar L to P substitutions with subsequent structural alterations are recognized human cancer markers (Kundu et al, 2013). We also found that 5 of the 30 SO-2 isolates were “Exceptional” in having an antrum-like median pH 50 of 4.4 (Figures 3A and 3B) but corpus-like affinities 20-fold and 50-fold higher than other antrum isolates at pH 6 and pH 4, respectively (Figure S3E).…”
Section: Resultsmentioning
confidence: 88%
“…However, L166 is invariant among vertebrates, and the L166P substitution is non-conservative, suggesting possible structural or functional effects on BPGM (Figure 2A). Furthermore, molecular modeling of L166P on the structure of BPGM predicts that P166 causes a major structural change, including the loss of a domain-linking a-helix (Figures 2B-2D; Kundu et al, 2013). BPGM is a 30-kDa protein that is known to be highly expressed in erythroid cells and RBC-rich organs (Pritlove et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Either of these could potentially affect HIF2A function and thereby influence traits associated with EPAS1. The substitution of proline for leucine is a particularly significant change that has been shown to cause functional disruptions in other proteins such as T4 lysozyme and caspase-9 37 , 38 . However, the impact of this substitution remains unknown.…”
Section: Discussionmentioning
confidence: 99%